Preparation method of modified cyanate ester resin

Through the preparation method of modified cyanate resin, combined with phosphocyanate and functional components, the problems of insufficient tensile strength and glass transition temperature of cyanate resin materials and poor flame retardant performance are solved, and the mechanical properties of the material are improved and the flame retardant performance are improved.

CN119823573AActive Publication Date: 2025-04-15THE RES INST FOR SPECIAL STRUCTURES OF AERONAUTICAL COMPOSITE AVIC

Patent Information

Application Number
CN202510114210.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-15
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The existing cyanate resin materials have problems such as small tensile strength, low glass transition temperature, and flame retardant performance needs to be improved.

Method used

The modified cyanate resin was obtained by the modification treatment, and the modified cyanate resin was prepared by combining functional components such as silicone phenol resin, modified montmorillonite and boron-containing carbon nanotubes.

Benefits of technology

It effectively increases the tensile strength of the resin, improves the glass transition temperature, and obtains good flame retardant properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to a preparation method of modified cyanate ester resin. Phosphorus-containing cyanate is obtained through modification treatment and is matched with functional components such as the silicon-containing phenolic resin, the modified montmorillonite and the boron-containing carbon nanotubes for common use, the modified cyanate resin is prepared, the tensile strength of the resin is effectively improved, the glass-transition temperature is increased, and meanwhile good flame retardance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and particularly relates to a preparation method of a modified cyanate ester resin. Background Art

[0002] Cyanate ester (CE) resin refers to a thermosetting resin containing two or more cyanate functional groups. When uncured, CE resin monomers are soluble in most common organic solvents, such as acetone solution, tetrahydrofuran and butanone solution. CE resin cured products have the following characteristics: high monomer cross-linking density and high crystallinity; small shrinkage of the cured product, good dimensional stability, high bending strength and tensile strength; small molecular chain dipole moment of the cured product, excellent and extremely low dielectric properties, etc., and can be used at higher temperatures. CE resin is widely used in high-frequency printed circuit boards, electronic and electrical engineering, and aerospace fields due to its good molding processability.

[0003] A Chinese patent (publication number CN114805801B) discloses a cyanate resin with low hygroscopicity and a preparation method thereof. The dimethyl paraphenylene type cyanate resin prepared by the invention introduces a group with low polarity and large volume into the cyanate structure, further reducing the polarity and water absorption of the resin; introducing an appropriate amount of bisphenol cyanate resin and silicone modified epoxy resin into the cyanate resin matrix is ​​structurally conducive to adjusting the crosslinking density, improving the conversion rate of functional groups, effectively reducing the residual polar groups caused by the curing of the resin, and reducing the water absorption of the resin. However, the patent does not solve the problems of low tensile strength, low glass transition temperature, and flame retardant properties of cyanate resin materials in the prior art, which seriously affects its actual use.

[0004] Therefore, how to modify the resin and introduce functional components to effectively increase the tensile strength of the modified cyanate ester resin, improve the glass transition temperature, and obtain good flame retardant properties has become a direction that needs to be focused on. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a modified cyanate ester resin, aiming to solve the problems of the cyanate ester resin materials in the prior art, such as low tensile strength, low glass transition temperature, and the need to improve flame retardant properties.

[0006] The present invention obtains phosphorus-containing cyanate by modification treatment, and uses it together with functional components such as silicon-containing phenolic resin, modified montmorillonite and boron-containing carbon nanotubes to prepare modified cyanate ester resin, which effectively increases the tensile strength of the resin, improves the glass transition temperature, and obtains good flame retardant properties.

[0007] The technical solution of the present invention is as follows:

[0008] The present invention provides a method for preparing a modified cyanate ester resin, comprising the following steps:

[0009] Step S1: adding 4 to 8 parts of (4-hydroxyphenyl) (diphenyl) phosphate to 200 to 240 parts of N, N-dimethylformamide by weight and stirring evenly, then adding 1 to 3 parts of sodium hydroxide, stirring at 26 to 30° C. for 2 to 4 hours, then adding 2 to 4 parts of epichlorohydrin, heating and reacting at 50 to 54° C. for 6 to 8 hours, cooling to room temperature, extracting with ethyl acetate, washing with water, drying, filtering, and distilling to obtain an intermediate product; prepolymerizing 8 to 10 parts of the intermediate product and 90 to 100 parts of bisphenol A cyanate at 106 to 110° C. for 10 to 30 minutes, and then removing bubbles at 120 to 130° C. for 60 to 80 minutes to obtain phosphorus-containing cyanate;

[0010] Step S2: In parts by weight, 80 to 90 parts of the phosphorus-containing cyanate ester and 10 to 20 parts of phenolic resin are mixed and heated to melt, and then 2 to 4 parts of phenolic compounds and 0.04 to 0.06 parts of catalysts are added at 80 to 100° C. and stirred for 20 to 30 minutes, and then 6 to 10 parts of montmorillonite and 4 to 8 parts of carbon nanotubes are added and stirred for 100 to 120 minutes to obtain a modified cyanate ester resin.

[0011] Phosphorus-containing cyanate is modified with epichlorohydrin to introduce epoxy groups. The high reactivity of the epoxy groups can increase the network density of the resin system, obtain strong interface bonding and disperse stress, prevent crack propagation, and thus improve the tensile strength of the resin material; at the same time, the introduced phosphate ester burns with the substrate under high temperature conditions to generate metaphosphoric acid with strong dehydration properties, non-volatile and high ignition point, which isolates the substrate from the air, reduces oxygen diffusion and heat transfer rates between the gas phase and the solid phase system, prevents combustion, and thus increases the oxygen index.

[0012] As a preferred technical solution of the present invention, the conditions for the heating and melting treatment include: a stirring speed of 1000 to 1500 r / min, a temperature of 100 to 120° C., and a time of 10 to 20 min.

[0013] As a preferred technical solution of the present invention, the phenolic compound is selected from a mixture of one or more of nonylphenol, p-aminophenol and 4-benzyloxyphenol.

[0014] As a preferred technical solution of the present invention, the catalyst is ferric acetylacetonate and dibutyltin dilaurate; the mass ratio of ferric acetylacetonate to dibutyltin dilaurate in the catalyst is (1-2):1.

[0015] As a preferred technical solution of the present invention, the phenolic resin is a silicon-containing phenolic resin; the preparation method of the silicon-containing phenolic resin comprises: adding 200 to 220 parts of phenol to 240 to 260 parts of formaldehyde by weight and stirring for 50 to 60 minutes, then adding 2 to 4 parts of tetraethyl orthosilicate and 2 to 4 parts of sodium carbonate, reacting at 80 to 90° C. for 60 to 90 minutes, adjusting the pH to 6.6 to 6.8 after the reaction is completed, and vacuum dehydrating to obtain the silicon-containing phenolic resin.

[0016] The active functional groups in the silicon-containing phenolic resin can react with the cyanate ester resin, thereby enhancing the interfacial interaction between the two phases and improving the overall mechanical properties of the material; at the same time, the silicon-containing component helps to increase the toughness of the matrix, reduce the possibility of crack propagation, and thus improve the tensile strength of the resin.

[0017] As a preferred technical solution of the present invention, the montmorillonite is modified montmorillonite; the preparation method of the modified montmorillonite comprises: adding 40 to 50 parts of montmorillonite to 100 to 140 parts of anhydrous ethanol by weight and dispersing them evenly, then adding 20 to 30 parts of dioctyldichlorosilane and stirring for 20 to 24 hours to obtain silylated montmorillonite; evenly mixing 40 to 50 parts of silylated montmorillonite and 100 to 120 parts of N,N-dimethylformamide, adding 20 to 24 parts of 3-hydroxyphthalic anhydride and 2 to 4 parts of sodium hydride for modification treatment to obtain modified montmorillonite.

[0018] As a preferred technical solution of the present invention, the conditions of the modification treatment include: temperature of 20 to 26° C. and time of 30 to 40 hours.

[0019] The modified montmorillonite increases the interlayer spacing of montmorillonite by introducing anhydride molecules, thereby obtaining a lamellar structure with a large specific surface area and a high aspect ratio. It can be evenly distributed in the cyanate resin matrix, restricting the movement of polymer chain segments, making it difficult for the molecular chains to rearrange during heating, thereby increasing the glass transition temperature of the resin material.

[0020] As a preferred technical solution of the present invention, the carbon nanotubes are boron-containing carbon nanotubes; the preparation method of the boron-containing carbon nanotubes comprises: adding 4 to 8 parts of carbon nanotubes by weight to 100 to 120 parts of isopropanol for ultrasonic dispersion for 40 to 60 minutes, then adding 40 to 50 parts of boric acid, stirring at 60 to 70° C. for 4 to 6 hours, and then calcining to obtain carbon nanotubes A; adding 4 to 8 parts of the carbon nanotubes A to a mixed solution of 20 to 30 parts of sulfuric acid and 20 to 30 parts of nitric acid, controlling the temperature to 80 to 90° C., stirring at a speed of 60 to 80 r / min, stirring for 6 to 8 hours, centrifuging, and drying to obtain boron-containing carbon nanotubes.

[0021] As a preferred technical solution of the present invention, the calcination treatment conditions include: placing in a nitrogen atmosphere, heating to 1200-1240° C., calcining for 1-3 hours, and then cooling to room temperature.

[0022] As a preferred technical solution of the present invention, the length of the carbon nanotubes is 1 to 3 μm.

[0023] The boron atoms introduced into the boron-containing carbon nanotubes can introduce more active sites on the surface of the carbon nanotubes and bond with the cyanate resin matrix to form a stronger interface bond, which limits the movement of polymer chain segments through strong interface interactions and increases the glass transition temperature of the resin material.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The phosphorus-containing cyanate of the present invention can not only combine with the hydroxyl group in the silicon-containing phenolic resin, but also react with the hydroxyl group of the silicon-containing phenolic resin and the carboxyl group generated after the surface of the boron-containing carbon nanotubes is acidified through the epoxy groups introduced by epichlorohydrin modification, thereby constructing a high-density network interpenetrating structure. Different materials in the network interpenetrating structure penetrate each other and are physically cross-linked, which increases the interaction force between interfaces, effectively disperses the external stress, prevents crack propagation, and improves the overall tensile strength of the material; at the same time, the network interpenetrating structure can effectively prevent the molecular chains from rearranging when heated, thereby improving the thermal stability and glass transition temperature of the entire system.

[0026] (2) The phosphorus-containing cyanate of the present invention can generate metaphosphoric acid with strong dehydration, low volatility and high ignition point under high temperature conditions, reducing oxygen diffusion and the mass and heat transfer rates between the gas phase and the solid phase system; the silicon element in the silicon-containing phenolic resin can promote the formation of a dense and stable carbon layer on the resin surface, effectively preventing the internal polymer from further decomposing and releasing volatile products; the modified montmorillonite can form an effective barrier in the polymer matrix when subjected to flame, preventing heat transfer, oxygen diffusion and the migration of combustible gases to the combustion area, thereby inhibiting the chain reaction during the combustion process; the boron-containing carbon nanotubes can increase the electron density on the surface of the carbon nanotubes by introducing the boron element, effectively capture highly reactive free radicals during the combustion process, and slow down the combustion process; through the synergy of multiple elements of phosphorus-silicon-boron and the combined effect of modified montmorillonite, the flame retardant properties of the resin are effectively improved.

[0027] (3) The phosphorus-containing cyanate of the present invention is modified by using epichlorohydrin to introduce epoxy groups. The high reactivity of the epoxy groups can increase the network density of the resin system, obtain strong interface bonding and disperse stress, prevent crack propagation, and thus improve the tensile strength of the resin material; at the same time, the introduced phosphate ester burns with the substrate under high temperature conditions to generate metaphosphoric acid with strong dehydration properties, low volatility and high ignition point, which isolates the substrate from the air, reduces oxygen diffusion and the mass and heat transfer rates between the gas phase and the solid phase system, prevents combustion, and thus improves the oxygen index.

[0028] (4) The active functional groups in the silicon-containing phenolic resin of the present invention can react with the cyanate ester resin, thereby enhancing the interfacial interaction between the two phases and improving the overall mechanical properties of the material; at the same time, the silicon-containing component helps to increase the toughness of the matrix, reduce the possibility of crack propagation, and thus improve the tensile strength of the resin.

[0029] (5) The modified montmorillonite of the present invention increases the interlayer distance of montmorillonite by introducing anhydride molecules, thereby obtaining a lamellar structure with a large specific surface area and a high aspect ratio, and can be evenly distributed in the cyanate resin matrix, restricting the movement of polymer chain segments, making it difficult for the molecular chains to rearrange during heating, thereby increasing the glass transition temperature of the resin material.

[0030] (6) The boron atoms introduced into the boron-containing carbon nanotubes of the present invention can introduce more active sites on the surface of the carbon nanotubes and bond with the cyanate resin matrix to form a stronger interface bond, thereby limiting the movement of polymer chain segments through strong interface interactions and increasing the glass transition temperature of the resin material. DETAILED DESCRIPTION

[0031] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0032] The sources of some components in the embodiments and comparative examples are as follows:

[0033] Bisphenol A cyanate ester, model C01MO, purchased from Yangzhou Tianqi New Materials Co., Ltd.;

[0034] Phenolic resin, model PF-8010, purchased from Shandong Shengquan New Materials Co., Ltd.;

[0035] Montmorillonite, model WSG-PN06, was purchased from Shanghai Wanzhao Fine Chemical Co., Ltd.;

[0036] Carbon nanotube I, model NC7000, length 2 μm, purchased from Nanocyl Company;

[0037] Carbon nanotube II, model MWNT-1020, length 15 μm, purchased from Shenzhen Nanoport Co., Ltd.;

[0038] Nonylphenol, CAS No. 84852-15-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0039] p-Aminophenol, CAS No. 123-30-8, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0040] 4-Benzyloxyphenol, CAS No. 103-16-2, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0041] Ferric acetylacetonate, CAS No. 14024-18-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0042] Dibutyltin dilaurate, CAS No. 77-58-7, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0043] (4-Hydroxyphenyl)(diphenyl)phosphate, CAS No. 56806-74-7, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0044] N,N-dimethylformamide, CAS No. 68-12-2, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0045] Sodium hydroxide, CAS No. 1310-73-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0046] Epichlorohydrin, CAS No. 106-89-8, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0047] Ethyl acetate, CAS No. 141-78-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0048] Phenol, CAS No. 108-95-2, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0049] Formaldehyde, CAS No. 50-00-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0050] Tetraethyl orthosilicate, CAS No. 78-10-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0051] Sodium carbonate, CAS No. 497-19-8, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0052] Dioctyldichlorosilane, CAS No. 18416-07-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0053] 3-Hydroxyphthalic anhydride, CAS No. 37418-88-5, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0054] Sodium hydride, CAS No. 7646-69-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0055] Boric acid, CAS No. 10043-35-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0056] Isopropyl alcohol, CAS No. 67-63-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0057] Nitric acid, CAS No. 7697-37-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0058] Example 1

[0059] This embodiment provides a method for preparing a modified cyanate ester resin, comprising the following steps:

[0060] Preparation of silicon-containing phenolic resin: By weight, 220 parts of phenol are added to 260 parts of formaldehyde and stirred for 60 minutes, then 4 parts of tetraethyl orthosilicate and 4 parts of sodium carbonate are added, and the reaction is carried out at 90°C for 60 minutes. After the reaction is completed, the pH is adjusted to 6.8, and vacuum dehydration is performed to obtain a silicon-containing phenolic resin.

[0061] Preparation of modified montmorillonite: By weight, 50 parts of montmorillonite are added to 140 parts of anhydrous ethanol and dispersed evenly, and then 30 parts of dioctyldichlorosilane are added and stirred for 24 hours to obtain silylated montmorillonite; 50 parts of silylated montmorillonite and 120 parts of N,N-dimethylformamide are mixed evenly, and 24 parts of 3-hydroxyphthalic anhydride and 4 parts of sodium hydride are added for modification treatment (temperature is 26°C, time is 30 hours) to obtain modified montmorillonite.

[0062] Preparation of boron-containing carbon nanotubes: In parts by weight, 8 parts of carbon nanotubes are added to 120 parts of isopropanol and ultrasonically dispersed for 60 minutes, then 50 parts of boric acid are added, stirred at 70°C for 4 hours, and then calcined. Place it in a nitrogen atmosphere, heat it to 1240°C and calcine it for 1 hour, and then cool it to room temperature to obtain carbon nanotubes A; 8 parts of the carbon nanotubes A are added to a mixed solution of 30 parts of sulfuric acid and 30 parts of nitric acid, the temperature is controlled at 90°C, the stirring speed is 80r / min, the reaction is stirred for 6 hours, centrifuged, and dried to obtain boron-containing carbon nanotubes.

[0063] Step S1: In parts by weight, 8 parts of (4-hydroxyphenyl) (diphenyl) phosphate are added to 240 parts of N, N-dimethylformamide and stirred evenly, then 3 parts of sodium hydroxide are added, stirred at 30°C for 2 hours, then 4 parts of epichlorohydrin are added, heated to react at 54°C for 6 hours, cooled to room temperature, extracted with ethyl acetate, washed with water, dried, filtered, and distilled to obtain an intermediate product; 10 parts of the intermediate product and 100 parts of bisphenol A cyanate are prepolymerized at 10°C for 10 minutes, and then bubbles are removed at 130°C for 60 minutes to obtain phosphorus-containing cyanate;

[0064] Step S2: In parts by weight, 90 parts of the phosphorus-containing cyanate ester and 20 parts of silicon-containing phenolic resin are mixed and heated to melt (stirring speed is 1500r / min, temperature is 120°C, time is 10min), then 4 parts of nonylphenol and 0.06 parts of catalyst (0.04 parts of ferric acetylacetonate and 0.02 parts of dibutyltin dilaurate) are added at 100°C and stirred for 30min, then 10 parts of modified montmorillonite and 8 parts of boron-containing carbon nanotubes are added and stirred for 120min to obtain modified cyanate ester resin.

[0065] Example 2

[0066] This embodiment provides a method for preparing a modified cyanate ester resin, comprising the following steps:

[0067] Preparation of silicon-containing phenolic resin: By weight, 200 parts of phenol are added to 240 parts of formaldehyde and stirred for 50 minutes, then 2 parts of tetraethyl orthosilicate and 2 parts of sodium carbonate are added, and the reaction is carried out at 80°C for 90 minutes. After the reaction is completed, the pH is adjusted to 6.6, and vacuum dehydration is performed to obtain a silicon-containing phenolic resin.

[0068] Preparation of modified montmorillonite: By weight, 40 parts of montmorillonite are added to 100 parts of anhydrous ethanol and dispersed evenly, and then 20 parts of dioctyldichlorosilane are added and stirred for 20 hours to obtain silylated montmorillonite; 40 parts of silylated montmorillonite and 100 parts of N,N-dimethylformamide are mixed evenly, and 20 parts of 3-hydroxyphthalic anhydride and 2 parts of sodium hydride are added for modification treatment (temperature is 20°C, time is 40 hours) to obtain modified montmorillonite.

[0069] Preparation of boron-containing carbon nanotubes: In parts by weight, 4 parts of carbon nanotubes are added to 100 parts of isopropanol and ultrasonically dispersed for 40 minutes, then 40 parts of boric acid are added, stirred at 60°C for 6 hours, and then calcined. Place it in a nitrogen atmosphere, heat it to 1200°C and calcine it for 3 hours, and then cool it to room temperature to obtain carbon nanotubes A; add 4 parts of the carbon nanotubes A to a mixture of 20 parts of sulfuric acid and 20 parts of nitric acid, control the temperature to 80°C, stir at a speed of 60r / min, stir the reaction for 8 hours, centrifuge, and dry to obtain boron-containing carbon nanotubes.

[0070] Step S1: In parts by weight, 4 parts of (4-hydroxyphenyl) (diphenyl) phosphate are added to 200 parts of N, N-dimethylformamide and stirred evenly, then 1 part of sodium hydroxide is added, stirred at 26°C for 4 hours, then 2 parts of epichlorohydrin are added, heated to react at 50°C for 8 hours, cooled to room temperature, extracted with ethyl acetate, washed with water, dried, filtered, and distilled to obtain an intermediate product; 8 parts of the intermediate product and 90 parts of bisphenol A cyanate are prepolymerized at 106°C for 30 minutes, and then bubbles are removed at 120°C for 80 minutes to obtain phosphorus-containing cyanate;

[0071] Step S2: In parts by weight, 80 parts of the phosphorus-containing cyanate ester and 10 parts of silicon-containing phenolic resin are mixed and heated to melt (stirring speed is 1000r / min, temperature is 100°C, time is 20min), then 2 parts of p-aminophenol and 0.04 parts of catalyst (0.02 parts of ferric acetylacetonate and 0.02 parts of dibutyltin dilaurate) are added at 80°C and stirred for 20min, then 6 parts of modified montmorillonite and 4 parts of boron-containing carbon nanotubes are added and stirred for 100min to obtain modified cyanate ester resin.

[0072] Example 3

[0073] This embodiment provides a method for preparing a modified cyanate ester resin, comprising the following steps:

[0074] Preparation of silicon-containing phenolic resin: By weight, 210 parts of phenol are added to 250 parts of formaldehyde and stirred for 55 minutes, then 3 parts of tetraethyl orthosilicate and 3 parts of sodium carbonate are added, and the reaction is carried out at 85°C for 80 minutes. After the reaction is completed, the pH is adjusted to 6.7, and vacuum dehydration is performed to obtain a silicon-containing phenolic resin.

[0075] Preparation of modified montmorillonite: In parts by weight, 45 parts of montmorillonite are added to 120 parts of anhydrous ethanol and dispersed evenly, and then 25 parts of dioctyldichlorosilane are added and stirred for 22 hours to obtain silylated montmorillonite; 45 parts of silylated montmorillonite and 110 parts of N,N-dimethylformamide are mixed evenly, and 22 parts of 3-hydroxyphthalic anhydride and 3 parts of sodium hydride are added for modification treatment (temperature is 24°C, time is 36 hours) to obtain modified montmorillonite.

[0076] Preparation of boron-containing carbon nanotubes: In parts by weight, 6 parts of carbon nanotubes are added to 110 parts of isopropanol and ultrasonically dispersed for 50 minutes, then 45 parts of boric acid are added, stirred at 65°C for 5 hours, and then calcined. Place it in a nitrogen atmosphere, heat it to 1220°C and calcine it for 2 hours, and then cool it to room temperature to obtain carbon nanotubes A; 6 parts of the carbon nanotubes A are added to a mixed solution of 25 parts of sulfuric acid and 25 parts of nitric acid, the temperature is controlled at 85°C, the stirring speed is 70r / min, the reaction is stirred for 7 hours, centrifuged, and dried to obtain boron-containing carbon nanotubes.

[0077] Step S1: In parts by weight, 6 parts of (4-hydroxyphenyl) (diphenyl) phosphate are added to 220 parts of N, N-dimethylformamide and stirred evenly, then 2 parts of sodium hydroxide are added, stirred at 28° C. for 3 hours, then 3 parts of epichlorohydrin are added, heated to react at 52° C. for 7 hours, cooled to room temperature, extracted with ethyl acetate, washed with water, dried, filtered, and distilled to obtain an intermediate product; 9 parts of the intermediate product and 95 parts of bisphenol A cyanate are prepolymerized at 108° C. for 20 minutes, and then bubbles are removed at 125° C. for 70 minutes to obtain phosphorus-containing cyanate;

[0078] Step S2: In parts by weight, 85 parts of the phosphorus-containing cyanate ester and 15 parts of the silicon-containing phenolic resin are mixed and heated to melt (stirring speed is 1200r / min, temperature is 110°C, time is 15min), and then 3 parts of 4-benzyloxyphenol and 0.05 parts of catalyst (0.03 parts of ferric acetylacetonate and 0.02 parts of dibutyltin dilaurate) are added at 90°C and stirred for 25min, and then 8 parts of modified montmorillonite and 6 parts of boron-containing carbon nanotubes are added and stirred for 110min to obtain a modified cyanate ester resin.

[0079] Comparative Example 1

[0080] This comparative example provides a method for preparing a cyanate ester resin, which differs from Example 1 in that commercially available bisphenol A type cyanate ester (model number C01MO) is used instead of phosphorus-containing cyanate ester.

[0081] Comparative Example 2

[0082] This comparative example provides a method for preparing a cyanate ester resin, which is different from Example 1 in that a commercially available phenolic resin (model PF-8010) is used instead of the silicon-containing phenolic resin.

[0083] Comparative Example 3

[0084] This comparative example provides a method for preparing a cyanate resin, which is different from Example 1 in that commercially available montmorillonite (model WSG-PN06) is used instead of modified montmorillonite.

[0085] Comparative Example 4

[0086] This comparative example provides a method for preparing a cyanate ester resin, which differs from Example 1 in that carbon nanotubes I are used instead of boron-containing carbon nanotubes.

[0087] Comparative Example 5

[0088] This comparative example provides a method for preparing a cyanate ester resin, which differs from Example 1 in that carbon nanotubes II are used instead of carbon nanotubes I to prepare boron-containing carbon nanotubes.

[0089] Comparative Example 6

[0090] This comparative example provides a method for preparing a cyanate resin, which is different from Example 1 in that the amount of ferric acetylacetonate in the catalyst is changed to 0.05 parts, and the amount of dibutyltin dilaurate is changed to 0.01 parts.

[0091] Comparative Example 7

[0092] This comparative example provides a method for preparing a cyanate ester resin, which is different from Example 1 in that the amount of ferric acetylacetonate in the catalyst is changed to 0.02 parts, and the amount of dibutyltin dilaurate is changed to 0.04 parts.

[0093] The performance of the cyanate resin provided in the above embodiments and comparative examples was tested, and the testing method was as follows:

[0094] (1) Tensile strength test: refer to the requirements of GB / T 2567-2021 Test method for properties of resin castings for testing.

[0095] (2) Glass transition temperature test: Test according to the requirements of GB / T 19466.2-2004 Plastics Differential Scanning Calorimetry (DSC) Part 2: Determination of glass transition temperature.

[0096] (3) Oxygen index test: The test shall be conducted in accordance with the requirements of GB / T 2406.2-2009 Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test.

[0097] The above performance test data is shown in Table 1.

[0098] Table 1 Performance test results

[0099] Tensile strength(MPa) Glass transition temperature(℃) Oxygen index (%) Example 1 98 203 30.1 Example 2 93 201 29.6 Example 3 96 202 29.9 Comparative Example 1 64 185 21.8 Comparative Example 2 71 189 22.6 Comparative Example 3 66 186 22.1 Comparative Example 4 69 188 22.3 Comparative Example 5 77 194 25.8 Comparative Example 6 82 196 26.5 Comparative Example 7 79 195 26.1

[0100] From the above content, it can be seen that the present invention obtains phosphorus-containing cyanate by modification treatment, and uses it together with functional components such as silicon-containing phenolic resin, modified montmorillonite and boron-containing carbon nanotubes to prepare modified cyanate ester resin (Examples 1 to 3), which has a tensile strength of 93 to 98 MPa, a glass transition temperature of 201 to 203°C, and an oxygen index of 29.6 to 30.1%.

[0101] Compared with Example 1, the use of commercially available bisphenol A cyanate (model C01MO) instead of phosphorus-containing cyanate reduces the tensile strength, reduces the glass transition temperature, and deteriorates the flame retardant properties (Comparative Example 1); Compared with Example 1, the use of commercially available phenolic resin (model PF-8010) instead of silicon-containing phenolic resin reduces the tensile strength, reduces the glass transition temperature, and deteriorates the flame retardant properties (Comparative Example 2); Compared with Example 1, the use of commercially available montmorillonite (model WSG-PN06) instead of modified montmorillonite reduces the tensile strength, reduces the glass transition temperature, and deteriorates the flame retardant properties (Comparative Example 3); Compared with Example 1, the use of carbon nanotubes I instead of boron-containing carbon nanotubes reduces the tensile strength, reduces the glass transition temperature, and deteriorates the flame retardant properties (Comparative Example 4); Compared with Example 1, the use of Carbon nanotubes II replace carbon nanotubes I to prepare boron-containing carbon nanotubes. Since the length of carbon nanotubes II is too large and the modification effect is not good, the tensile strength is reduced, the glass transition temperature is reduced, and the flame retardant properties are deteriorated (Comparative Example 5); compared with Example 1, the amount of ferric acetylacetonate in the catalyst is changed to 0.05 parts, and the amount of dibutyltin dilaurate is changed to 0.01 parts. Since the amount of ferric acetylacetonate is too much and the compounding effect is not good, the tensile strength is reduced, the glass transition temperature is reduced, and the flame retardant properties are deteriorated (Comparative Example 6); compared with Example 1, the amount of ferric acetylacetonate in the catalyst is changed to 0.02 parts, and the amount of dibutyltin dilaurate is changed to 0.04 parts. Since the amount of ferric acetylacetonate is too little, the compounding effect is not good, the tensile strength is reduced, the glass transition temperature is reduced, and the flame retardant properties are deteriorated (Comparative Example 7).

[0102] In summary, the present invention obtains phosphorus-containing cyanate through modification treatment, and uses it together with functional components such as silicon-containing phenolic resin, modified montmorillonite and boron-containing carbon nanotubes to prepare modified cyanate ester resin, which effectively increases the tensile strength of the resin, improves the glass transition temperature, and obtains good flame retardant properties.

Claims

1. A method for preparing a modified cyanate ester resin, characterized in that: The following steps are involved: Step S1: adding 4 to 8 parts of (4-hydroxyphenyl) (diphenyl) phosphate to 200 to 240 parts of N, N-dimethylformamide by weight and stirring evenly, then adding 1 to 3 parts of sodium hydroxide, stirring at 26 to 30° C. for 2 to 4 hours, then adding 2 to 4 parts of epichlorohydrin, heating and reacting at 50 to 54° C. for 6 to 8 hours, cooling to room temperature, extracting with ethyl acetate, washing with water, drying, filtering, and distilling to obtain an intermediate product; prepolymerizing 8 to 10 parts of the intermediate product and 90 to 100 parts of bisphenol A cyanate at 106 to 110° C. for 10 to 30 minutes, and then removing bubbles at 120 to 130° C. for 60 to 80 minutes to obtain phosphorus-containing cyanate; Step S2: In parts by weight, 80 to 90 parts of the phosphorus-containing cyanate ester and 10 to 20 parts of phenolic resin are mixed and heated to melt, and then 2 to 4 parts of phenolic compounds and 0.04 to 0.06 parts of catalysts are added at 80 to 100° C. and stirred for 20 to 30 minutes, and then 6 to 10 parts of montmorillonite and 4 to 8 parts of carbon nanotubes are added and stirred for 100 to 120 minutes to obtain a modified cyanate ester resin.

2. The method for preparing a modified cyanate ester resin according to claim 1, characterized in that: The conditions for the heating and melting treatment include: a stirring speed of 1000 to 1500 r / min, a temperature of 100 to 120° C., and a time of 10 to 20 min.

3. The method for preparing a modified cyanate ester resin according to claim 1, characterized in that: The phenolic compound is selected from a mixture of one or more of nonylphenol, p-aminophenol and 4-benzyloxyphenol.

4. The method for preparing a modified cyanate ester resin according to claim 1, characterized in that: The catalyst is ferric acetylacetonate and dibutyltin dilaurate; the mass ratio of ferric acetylacetonate to dibutyltin dilaurate in the catalyst is (1-2):

1.

5. The method for preparing a modified cyanate ester resin according to claim 1, characterized in that: The phenolic resin is a silicon-containing phenolic resin; The preparation method of the silicon-containing phenolic resin comprises: adding 200 to 220 parts of phenol to 240 to 260 parts of formaldehyde by weight, stirring for 50 to 60 minutes, then adding 2 to 4 parts of tetraethyl orthosilicate and 2 to 4 parts of sodium carbonate, reacting at 80 to 90° C. for 60 to 90 minutes, adjusting the pH to 6.6 to 6.8 after the reaction is completed, and vacuum dehydrating to obtain the silicon-containing phenolic resin.

6. The method for preparing a modified cyanate ester resin according to claim 1, characterized in that: The montmorillonite is modified montmorillonite; The preparation method of the modified montmorillonite comprises: adding 40 to 50 parts of montmorillonite to 100 to 140 parts of anhydrous ethanol by weight and dispersing the mixture uniformly, and then adding 20 to 30 parts of dioctyldichlorosilane and stirring the mixture for 20 to 24 hours to obtain silylated montmorillonite; and uniformly mixing 40 to 50 parts of silylated montmorillonite and 100 to 120 parts of N,N-dimethylformamide, and then adding 20 to 24 parts of 3-hydroxyphthalic anhydride and 2 to 4 parts of sodium hydride for modification to obtain the modified montmorillonite.

7. The method for preparing a modified cyanate ester resin according to claim 6, characterized in that: The modification treatment conditions include: temperature of 20-26° C. and time of 30-40 hours.

8. The method for preparing a modified cyanate ester resin according to claim 1, characterized in that: The carbon nanotubes are boron-containing carbon nanotubes; The preparation method of the boron-containing carbon nanotubes comprises: adding 4 to 8 parts of carbon nanotubes by weight to 100 to 120 parts of isopropanol for ultrasonic dispersion for 40 to 60 minutes, then adding 40 to 50 parts of boric acid, stirring at 60 to 70° C. for 4 to 6 hours, and then calcining to obtain carbon nanotubes A; adding 4 to 8 parts of the carbon nanotubes A to a mixed solution of 20 to 30 parts of sulfuric acid and 20 to 30 parts of nitric acid, controlling the temperature to 80 to 90° C., stirring at 60 to 80 r / min, stirring for 6 to 8 hours, centrifuging, and drying to obtain the boron-containing carbon nanotubes.

9. The method for preparing a modified cyanate ester resin according to claim 8, characterized in that: The calcination treatment conditions include: placing in a nitrogen atmosphere, heating to 1200-1240° C. for calcination for 1-3 hours, and then cooling to room temperature.

10. The method for preparing a modified cyanate ester resin according to claim 8, characterized in that: The length of the carbon nanotubes is 1 to 3 μm.

Citation Information

Patent Citations

  • A cyanate ester resin with low hygroscopicity and its preparation method

    CN114805801B

  • Cyanic acid ester compound, method for producing same, resin composition and cured product

    CN107075090A

  • High-toughness halogen-free cyanate composite material and preparation method thereof

    CN110218445A

  • Preparation method of modified cyanate ester resin with atomic oxygen irradiation resistance

    CN110982264A

  • Polycarboxyl modified montmorillonite in-situ polymerization nylon 6 composite material and preparation method thereof

    CN114262514A

Cited By

  • Laser edge sealing strip and production process thereof

    CN120424392A